The association between body image, emotional health, relationships, and unhealthy dietary behaviors among medical sciences students: A structural equation modeling analysis - Hoda Arabi‐Mianrood; Zohreh Shahhosseini; Monirolsadate Hosseini Tabaghdehi (Wiley, 2022)
Abstract Aim Although it showed that poor body image may drive an individual to unhealthy dietary behaviors, but less is known about the role of emotional health and interpersonal relationships in this regard in different age group of population. This study aimed to investigate the association between body image, emotional health, relationships, and unhealthy dietary behaviors among medical sciences students. Methods In this cross‐sectional study, using a three‐stage stratified sampling method, 248 Iranian medical sciences students were recruited. The participants completed self‐administered questionnaires, including Youth Risk Behavior Survey Questionnaire, Adolescent Health Concerns Inventory, and Body Image Concern Inventory. The data were analyzed using SPSS‐20 and structural equation modeling in the Amos software version 24. Results The results indicate the acceptability of the goodness of fit model index. Direct association of body image with emotional health (β = 0.91, p = 0.005) and relationships (β = 0.88, p = 0.009) was significant, but any direct and indirect association between body and unhealthy dietary behaviors was not found. Conclusion This study underlines the importance of being aware of the association between body image, emotional health, and relationships Further studies are recommended to explore the relationship between these factors and unhealthy dietary behaviors in medical sciences students.